Extreme relativistic electron fluxes in the Earth's outer radiation belt: Analysis of INTEGRAL IREM data. Issue 7 (27th July 2017) - Meredith, Nigel P.; Horne, Richard B.; Sandberg, Ingmar; Papadimitriou, Constantinos; Evans, Hugh D. R.
Abstract: Relativistic electrons ( E > 500 keV) cause internal charging and are an important space weather hazard. To assess the vulnerability of the satellite fleet to these so‐called "killer" electrons, it is essential to estimate reasonable worst cases, and, in particular, to estimate the flux levels that may be reached once in 10 and once in 100 years. In this study we perform an extreme value analysis of the relativistic electron fluxes in the Earth's outer radiation belt as a function of energy and L ∗ . We use data from the Radiation Environment Monitor (IREM) on board the International Gamma Ray Astrophysical Laboratory (INTEGRAL) spacecraft from 17 October 2002 to 31 December 2016. The 1 in 10 year flux at L ∗ =4.5, representative of equatorial medium Earth orbit, decreases with increasing energy ranging from 1.36 × 10 7 cm −2 s −1 sr −1 MeV −1 at E = 0.69 MeV to 5.34 × 10 5 cm −2 s −1 sr −1 MeV −1 at E = 2.05 MeV. The 1 in 100 year flux at L ∗ =4.5 is generally a factor of 1.1 to 1.2 larger than the corresponding 1 in 10 year flux. The 1 in 10 year flux at L ∗ =6.0, representative of geosynchronous orbit, decreases with increasing energy ranging from 4.35 × 10 6 cm −2 s −1 sr −1 MeV −1 at E = 0.69 MeV to 1.16 × 10 5 cm −2 s −1 sr −1 MeV −1 at E = 2.05 MeV. The 1 in 100 year flux at L ∗ =6.0 is generally a factor of 1.1 to 1.4 larger than the corresponding 1 in 10 year flux. The ratio of the 1 in 10 year flux at L ∗ =4.5 to that at L ∗ =6.0 increases with increasing energy ranging from 3.1 at E = 0.69 MeV to 4.6 at E = 2.05 MeV. Key Points: The 1 in 10 year flux at L * = 6.0 ranges from 4.35 × 10 6 cm −2 s −1 sr −1 MeV −1 at E = 0.69 MeV to 1.16 × 10 5 cm −2 s −1 sr −1 MeV −1 at E = 2.05 MeV The ratio of the 1 in 10 year flux at L * = 6.0 to that at L * = 4.0 ranges from 3.1 at E = 0.69 MeV to 4.6 at E = 2.05 MeV The 1 in N year electron fluxes as a function of energy and L * can serve as benchmarks against which to compare other extreme events